Costs of Hemodialysis and Kidney Transplantation in Sudan: A Single Center Experience (Iranian Journal of Kidney Diseases, 2010)
Introduction. End-stage renal disease is a serious illness with major consequences in both health and healthcare expenditures. The growing number of patients with end-stage renal disease in developing countries will consume a greater proportion of healthcare budget. We aimed to assess the costs of hemodialysis and kidney transplantation in a renal care center in Sudan.Materials and Methods. We conducted a cross-sectional study to estimate the costs of kidney transplantation and compare those with the costs of hemodialysis per year. We enrolled 78 patients on regular hemodialysis for at least 2 years and 33 kidney transplant patients on regular follow-up at Gezira Hospital for Renal Diseases and Surgery in Sudan.Results. The annual cost of hemodialysis was found to be US $ 6847.00. The total cost of the first year after transplantation was US $ 14 825.04 and the cost of kidney transplantation after the first year was US $ 10 651.00. The total hospitalization days and absence from work were less in the transplant group.Conclusions. Hemodialysis in Sudan is less expensive than transplantation.